Real‐time COVID‐19 detection over chest x‐ray images in edge computing. (30th April 2022) - Xu, Weijie; Chen, Beijing; Shi, Haoyang; Tian, Hao; Xu, Xiaolong
Abstract: Severe Coronavirus Disease 2019 (COVID‐19) has been a global pandemic which provokes massive devastation to the society, economy, and culture since January 2020. The pandemic demonstrates the inefficiency of superannuated manual detection approaches and inspires novel approaches that detect COVID‐19 by classifying chest x‐ray (CXR) images with deep learning technology. Although a wide range of researches about bran‐new COVID‐19 detection methods that classify CXR images with centralized convolutional neural network (CNN) models have been proposed, the latency, privacy, and cost of information transmission between the data resources and the centralized data center will make the detection inefficient. Hence, in this article, a COVID‐19 detection scheme via CXR images classification with a lightweight CNN model called MobileNet in edge computing is proposed to alleviate the computing pressure of centralized data center and ameliorate detection efficiency. Specifically, the general framework is introduced first to manifest the overall arrangement of the computing and information services ecosystem. Then, an unsupervised model DCGAN is employed to make up for the small scale of data set. Moreover, the implementation of the MobileNet for CXR images classification is presented at great length. The specific distribution strategy of MobileNet models is followed. The extensive evaluations of the experiments demonstrate the efficiency and accuracy of the proposed scheme for detecting COVID‐19 over CXR images in edge computing.